Open neural tube defect: A case report - Mejias Quintero, Mileidy Egleet (2018)
Neural tube defects are the second most frequent cause of congenital malformation during prenatal development. They constitute 10% of them. The origin is usually multifactorial, and it results in an incomplete or defective closure of the anterior or posterior neuropore, causing different levels of defects in the central nervous system. Despite all the research done, our knowledge of genetics in this topic is very limited so we don’t know how many genes can confer risk of anomaly in the development of the neural tube. Diagnosis is mainly based on the ultrasound study of the central nervous system generally during the second trimester. Nevertheless, assessment in the first trimester allows us a fairly reliable diagnostic approach by means of the echographic markers described a few years ago. Once the diagnosis is confirmed, and if abortion is allowed in the country, the management depends on the parents’ willingness to continue or not with the gestation. In case of continuing with it, there are options for intrauterine or post-natal surgical treatment. The prognosis of this malformation is usually variable and depends on location, size and its association or not with hydrocephalus.